simplify

(3x^{2}+9x-1)+(-5x^{2}+6x-10)

A. 8𝑥2 − 3𝑥 + 9

B. −2𝑥2 − 3𝑥 + 9

C. 8𝑥2 + 15𝑥 − 11

D. −2𝑥2 + 15𝑥 − 11

Guest Aug 29, 2017

#1**+3 **

(3x^{2} + 9x - 1) + (-5x^{2} + 6x - 10)

We can get rid of the parenthesees since there is only addition between them.

= 3x^{2} + 9x - 1 + -5x^{2} + 6x - 10

Now we can rearrange the terms so like terms are together.

= 3x^{2} - 5x^{2} + 9x + 6x - 1 - 10

Combine like terms. Just like 3 apples - 5 apples = -2 apples ....so does 3x^{2} - 5x^{2} = -2x^{2}

= -2x^{2} + 15x - 11

hectictar
Aug 29, 2017

#1**+3 **

Best Answer

(3x^{2} + 9x - 1) + (-5x^{2} + 6x - 10)

We can get rid of the parenthesees since there is only addition between them.

= 3x^{2} + 9x - 1 + -5x^{2} + 6x - 10

Now we can rearrange the terms so like terms are together.

= 3x^{2} - 5x^{2} + 9x + 6x - 1 - 10

Combine like terms. Just like 3 apples - 5 apples = -2 apples ....so does 3x^{2} - 5x^{2} = -2x^{2}

= -2x^{2} + 15x - 11

hectictar
Aug 29, 2017